Queen's Park Hotel, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The Queen's Park Hotel, located in Port of Spain on the Southern side of the Queen's Park Savannah, was first opened in January 1895. The arched sign "Queen's Park Hotel" can be seen at the entrance at far right.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; [1901]; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Transportation--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)